IMPLEMENTASI ENTERPRISE APPLICATION INTEGRATION (EAI) DALAM PEMODELAN SISTEM INFORMASI BACK OFFICE PADA RESTO : “WARUNG PELIPUR LARA” BERBASIS WEB - Rizki Ananda; Christian Tonyjanto; Agus Tommy Adi Prawira; Aulia Iefan Datya (Jurnal Teknologi Informasi dan Komputer, 2020)
ABSTRACTEnterprise Application Integration (EAI) plays a role in supporting the business process that enabling well-integrated management. Raw material inventory in Warung Pelipur Lara has not been systemized yet so that the management of inventory, report, and raw material purchase transactions to suppliers have not neatly arranged. The back office Information system of Warung Pelipur Lara uses The Enterprise Application Integration (EAI) method with a waterfall design. All data contained in Warung Pelipur Lara information system impact on decision making by the management in managing Warung Pelipur Lara. Manual data that input into the database, namely, data inventory of raw material, sales report, and raw material purchase report. Human Resource skills can affect each transaction process and report, therefore the back-office information system at this restaurant to be expected to support restaurant operations in the specified aspects. From the design of Warung Pelipur Lara back-office information system is expected to be able to improve inventory management with designated and straightforward features.Keywords: Enterprise Application Integration (EAI), Waterfall Method, Database, Inventory Information SystemABSTRAKEnterprise Application Integration (EAI) berperan penting dalam mendukung proses bisnis yang memungkinkan pengelolaan manajemen terintegrasi dengan baik. Manajemen inventaris bahan baku pada Warung Pelipur Lara masih belum tersistem sehingga pengorganisasian inventaris, laporan dan transaksi pembelian bahan baku ke supplier belum tersusun secara rapi.Sistem informasi back office pada Warung Pelipur Lara menggunakan metode Enterprise Application Integration (EAI) dengan rancangan waterfall. Seluruh data yang terdapat di sistem informasi Warung Pelipur Lara berpengaruh pada pengambilan keputusan oleh pihak manajemen dalam pengelolaan Warung Pelipur Lara. Data – data manual yang diinputkan ke dalam database antara lain: data inventaris bahan baku, laporan penjualan dan laporan pembelian bahan baku. Kemampuan Sumber Daya Manusia (SDM) dapat mempengaruhi setiap proses transaksi dan laporan, sehingga sistem informasi back office resto ini diharapkan dapat mendukung operasional resto dalam aspek – aspek yang sudah ditentukan.Dari perancangan sistem informasi back office Warung Pelipur Lara ini diharapkan dapat memperbaiki manajemen pengelolaan inventaris dengan fitur – fitur yang sudah dirancang dan mudah digunakan.Kata kunci: Enterprise Application Integration (EAI), metode waterfall, basis data, sistem informasi inventaris